2018
DOI: 10.1002/mp.12987
|View full text |Cite
|
Sign up to set email alerts
|

Data‐driven gating in PET: Influence of respiratory signal noise on motion resolution

Abstract: The SNR can serve as a general metric to assess the success of COM-based DDG, even in different scanners and patients. The derived formula for motion resolution can be used to estimate the actual motion extent reasonably well in cases of limited PET raw data statistics. This may be of interest for individualized radiotherapy treatment planning procedures of target structures subjected to respiratory motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…It may be possible to devise improved measures of the suitability of DDG waveforms for respiratory gating, as well as the benefit that may be expected from applying such gating. Different metrics which have some similarity to R have been used in the evaluation of other DDG algorithms [19, 20]. The phantom study confirmed that larger motion amplitudes do lead to higher R values but also showed that the increase was not linear.…”
Section: Discussionmentioning
confidence: 98%
“…It may be possible to devise improved measures of the suitability of DDG waveforms for respiratory gating, as well as the benefit that may be expected from applying such gating. Different metrics which have some similarity to R have been used in the evaluation of other DDG algorithms [19, 20]. The phantom study confirmed that larger motion amplitudes do lead to higher R values but also showed that the increase was not linear.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, list‐mode event‐driven methods were shown to have the capability to detect respiratory and/or cardiac motion signals . A similar technique was applied to detect rigid head movement with time‐of‐flight (TOF) information .…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, our group published an article discussing potential of a real-time DDMC system and demonstrated this can be achieved by collapsing pre-reconstructed data space into more manageable data structures [5]. Since then, there have been numerous additions and contributions to developing DDMC ([611]). These articles demonstrate that robust DDMC is possible, though its practical, clinical implementation remains a systems integration challenge.…”
Section: Introductionmentioning
confidence: 99%